Molecular epidemiology of Porcine Reproductive and Respiratory Syndrome Virus causing outbreaks in Karnataka - CHANDRANAIK, B M; SHETTY, VASANTHKUMAR; GIRIDHAR, P; REDDY, POORVI; MEGHANA, P; VENKATESHA, M D; BYREGOWDA, S M (The Indian Journal of Animal Sciences, 2019)
We describe the molecular epidemiology of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) involved in outbreaks and massive spread of Porcine Reproductive and Respiratory Syndrome (PRRS) in Karnataka state of India during the year 2017. The study involved investigation of outbreaks in three districts.viz, Udupi, Dakshina kannada and Bengaluru in Karnataka. The disease was characterised by large scale piglet mortality with severe respiratory distress and abortions in pregnant sows. The study recorded death of 394 piglets, 131 adults and abortions in 82 pregnant sows. The organ samples collected from dead pigs were found negative for Classical swine fever virus by 5’UTR gene based Reverse transcription polymerase chain reaction (RT-PCR). RT-PCR targeting full length ORF5 gene of PRRSV on spleen and lung samples of dead pigs yielded specific amplicon of 803 bp indicating the presence of PRRSV. The phylogenetic analysis of the nucleotide sequences derived from ORF5 gene of PRRSV involved in the current outbreaks revealed 99.99% sequence homology with the highly pathogenic PRRSV of genotype 2 (North American type) from China and India (Mizoram state). Since pig husbandry plays a significant role in socio-economic upliftment of the poor and marginalised farmers in the country, it’s time to put in place effective prevention and control measures for PRRS, before it cripples pig industry in India and its surrounding world. Present study is the first epidemiological report of PRRS outbreaks in South India.